The Possibility of Fidelity in Adaptations: The Case of Director Michael Haneke - Alper Keleş (Skad)
This study seeks an answer to the question of whether the content of the novel or the interpretation of the novel content by a director is followed in film adaptations, how clear the boundaries of film narrative and literary narrative are, the reflections of the narrative techniques specific to these media in the two media, how effective the narrative features are at the level of the audience and the reader, and to what extent the audience is provided with the interpretation space allocated at the end of the films. The methodology used is determined by creating a common research area in both fields with the help of the concepts of cinema and literature, as emphasized in the theories of intermediality. This article, consisting of ideas specific to the fields of the two media, explains how searching for the literary text in adaptation films is an appropriate approach with the example of Michael Haneke's adaptation of Franz Kafka's The Castle.